2018
DOI: 10.3389/fphys.2018.00277
|View full text |Cite
|
Sign up to set email alerts
|

Fitness Level and Not Aging per se, Determines the Oxygen Uptake Kinetics Response

Abstract: Although aging has been associated to slower trueV˙O2 kinetics, some evidence indicates that fitness status and not aging per se might modulate this response. The main goal of this study was to examine the trueV˙O2, deoxygenated hemoglobin+myoglobin (deoxy-[Hb+Mb]) kinetics, and the NIRS-derived vascular reperfusion responses in older compared to young men of different training levels (i.e., inactive, recreationally active, and endurance trained). Ten young inactive [YI; 26 ± 5 yrs.; peak trueV˙O2 (trueV˙O2pea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 63 publications
(110 reference statements)
0
24
0
Order By: Relevance
“…Thus, properly assessing vascular function within conduit artery and the microvascular circulation is important for prevention, early detection, and monitoring of CVD . In relation to this, the use of near‐infrared spectroscopy (NIRS) combined with vascular occlusion test (VOT) technique (NIRS‐VOT) has been demonstrated to be a useful tool for assessment of microvascular function . This technique evaluates microvascular reactivity by assessing the steepness of the upslope of the muscle oxygen saturation signal (reperfusion slope, % per s), typically following a 5‐min period of limb occlusion .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, properly assessing vascular function within conduit artery and the microvascular circulation is important for prevention, early detection, and monitoring of CVD . In relation to this, the use of near‐infrared spectroscopy (NIRS) combined with vascular occlusion test (VOT) technique (NIRS‐VOT) has been demonstrated to be a useful tool for assessment of microvascular function . This technique evaluates microvascular reactivity by assessing the steepness of the upslope of the muscle oxygen saturation signal (reperfusion slope, % per s), typically following a 5‐min period of limb occlusion .…”
Section: Introductionmentioning
confidence: 99%
“…the use of near-infrared spectroscopy (NIRS) combined with vascular occlusion test (VOT) technique (NIRS-VOT) has been demonstrated to be a useful tool for assessment of microvascular function. [4][5][6][7][8][9][10][11][12][13] This technique evaluates microvascular reactivity by assessing the steepness of the upslope of the muscle oxygen saturation signal (reperfusion slope, % per s), typically following a 5-min period of limb occlusion. 7,10,11 The NIRS-VOT approach has been shown to provide repeatable and reliable measures of vascular responsiveness within the lower and upper limb microvasculature, 14,15 and to offer a noninvasive and "low-cost" alternative to the most commonly used methods of microvascular function assessment (ie, blood flow response to vasoactive substances assessed by Doppler ultrasound).…”
mentioning
confidence: 99%
“…In healthy adults, the acceleration of τV̇O2 has been reported to occur in the early period of endurance training, and V̇O2 at peak exercise can subsequently increase [20,21]. Additionally, a previous study reported that τV̇O2 was shorter in the recreationally active group than in the inactive group; however, there was no significant difference in V̇O2 at peak exercise between the two groups [19]. These results of previous studies indicated that τV̇O2 was more sensitive than V̇O2 at peak exercise in assessing cardiorespiratory functional changes, which may explain our results that a higher FSS score was significantly correlated with a longer τV̇O2 but not with V̇O2 at peak exercise.…”
Section: Discussionmentioning
confidence: 86%
“…The submaximal constant-load exercise test started with resting on the cycle ergometer for 3 min, followed by performing exercise at 80% of the workload corresponding to the ventilatory threshold for 6 min [19,34]. The protocol was repeated three times, with a rest between each repetition.…”
Section: Exercise Testingmentioning
confidence: 99%
See 1 more Smart Citation